MENINGKATKAN PENGETAHUAN SAINS ANAK MELALUI PENDEKATAN EKSPLORASI LINGKUNGAN DI TK SWASTA PGRI DESA TIGA ALUR KECAMATAN PANGKALAN JAMBU KABUPATEN MERANGIN - Okta Delita; Dien Muhammad Ismal Bransika (LP3M | STKIP YPM Bangko, 2022)
Kindergarten education has an important role in developing the personality of early childhood. The development of science in kindergarten children will develop logical thinking skills that are not possessed by children. Learning at the PGRI Tiga Alur Village Kindergarten, Pangkalan Jambu District, using the environmental exploration approach is still rarely done in the PGRI Tiga Alur Village Private Kindergarten, Pangkalan Jambu Village, Merangin Regency and is not focused on improving children's science knowledge, only 5 children or 20% of children's attainment in knowledge science. The purpose of this study was to describe the increase in children's science knowledge through the environmental exploration approach in the PGRI Private Kindergarten in Tiga Alur Village, Pangkalan Jambu District, Merangin Regency, 2019/2020 Academic Year. This research uses classroom action research.. The results after learning by using an exploration approach to the surrounding environment, children's science knowledge in the learning process increases. In the first cycle of meeting 1, the teacher's activity was only 37.5%, this was because the teacher had not been able to master the class, while at the second meeting until the end of the second cycle the teacher had mastered the class, as shown by the teacher's activity had been 100% achieved. From the research results it can be concluded that the average achievement of children in the first cycle of meeting 2 only reached 60% and in the second cycle of meeting 2 it increased to 93%.